2020
DOI: 10.1186/s13052-020-00842-3
|View full text |Cite
|
Sign up to set email alerts
|

What a paediatrician should know about congenital clubfoot

Abstract: Clubfoot is the most frequent congenital malformation of the foot, affecting more than 1–2 subjects per 1.000 newborns. Without appropriate treatment, a child with congenital clubfoot will never be able to walk physiologically with a dramatic impact on the quality of life. In the last decades, different corrective solutions have been proposed, and there is rising scientific evidence that the Ponseti non-invasive method is safe and effective in the treatment of the clubfoot. So, what should a general paediatric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…2 Additionally, when asked which approach of clubfoot management the Ponseti technique and preferred surgery 57.6 percent of participants chose Ponseti technique, where as 19.3 percent chose the surgery. 3 Our findings revealed that 1.2% of the respondents were unsure about the ideal timing to begin clubfoot treatment. 32.8 percent of participants said it was ideal to begin therapy between 6 and 12 months, while 37.7 percent said it should be given before the age of six months.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…2 Additionally, when asked which approach of clubfoot management the Ponseti technique and preferred surgery 57.6 percent of participants chose Ponseti technique, where as 19.3 percent chose the surgery. 3 Our findings revealed that 1.2% of the respondents were unsure about the ideal timing to begin clubfoot treatment. 32.8 percent of participants said it was ideal to begin therapy between 6 and 12 months, while 37.7 percent said it should be given before the age of six months.…”
Section: Discussionmentioning
confidence: 67%
“…However, delaying the problem's treatment makes it difficult to offer non-surgical care. 3 The mainstream of clubfoot diagnoses are made clinically; radiography was not always necessary. Additionally, prenatal diagnosis can be performed using ultrasonography.…”
Section: Introductionmentioning
confidence: 99%
“…[3] . The overall incidence of 1 in 1000 live births [3,5] . Eighty percent of the time, clubfoot is the only visible abnormality [1,3] .…”
Section: Discussionmentioning
confidence: 99%
“…If left untreated, the deformity will persist into adulthood and severely impair life quality [ 219 ]. Dibello et al elucidated that early recognition of the deformity and immediate referral to the orthopedic specialist are the key elements for effective treatment [ 220 ]. If clubfoot was detected, a local orthopedic surgeon should be contacted to establish prompt referral to a clubfoot center, preferably within 48 h but no longer than 1 week after delivery.…”
Section: Introductionmentioning
confidence: 99%